Indicators for local health plan monitoring and evaluation: A modified Delphi consensus. Issue 4 (21st December 2021) - Santos, João Vasco; Martins, Filipa Santos; Vidal‐Castro, Joana; Silva‐Rocha, Sofia; Areias, Rita; Oliveira, António; Santos, Sandra; Lamelas, Cristina; Amorim, Helena; Martins, Alexandra; Vieira, Mariana; Ramos, João Pedro; et al.
Abstract: Objective: There is still a lack of health indicators for monitoring and evaluating health planning at the local level. In Portugal, local health plans (LHP) include a prioritized set of health priorities, which should be monitored and evaluated. This study is an example of a low‐resource method to identify and reuse indicators for LHP monitoring and evaluation already collected for other purposes. Design and sample: A modified Delphi consensus method was applied, with three rounds of email rating questionnaires and a final meeting, between January 2018 and January 2019. The Delphi panel consisted of eight members from the Planning and Administration Group of the Espinho/Gaia Local Public Health Unit. Measurements: Panelists were asked to assess the indicators' validity for monitoring diseases/determinants from a pre‐selected list of potential binomials between 140 PHC indicators and 15 diseases/determinants. Results: After four rounds, there was consensus in considering 141 binomials (34.0%) as appropriate, diabetes mellitus being the disease with more appropriate indicators. Conclusion: This study portrays the applicability of a commonly used, easy and low‐resource method in a Portuguese Local Public Health Unit to select and reuse primary health care indicators for LHP monitoring and evaluation.